Differences in the mass and quality of the quadriceps with age and sex and their relationships with knee extension strength. Issue 4 (19th May 2021) - Mizuno, Takafumi; Matsui, Yasumoto; Tomida, Makiko; Suzuki, Yasuo; Nishita, Yukiko; Tange, Chikako; Shimokata, Hiroshi; Imagama, Shiro; Otsuka, Rei; Arai, Hidenori
Abstract: Background: Although muscle quality evaluations are currently considered important for diagnosing sarcopenia, data from the general population are lacking. This study used mid‐thigh computed tomography measurements to evaluate age‐related and sex‐related differences in quadriceps femoris muscle quality and mass and their relationships with knee extension strength (KES). Methods: Cross‐sectional data from 520 Japanese individuals (273 men and 247 women, mean age: 63.1 ± 10.6 years) were analysed. Mass and quality were assessed using quadriceps cross‐sectional areas (CSAs) and computed tomography values (CTVs), respectively. The four constituent muscles, intermuscular adipose tissue, and entire quadriceps area (total quadriceps muscles + intermuscular adipose tissue) were assessed, and the data were stratified by five age groups and sex. To evaluate age‐related decline, linear and quadratic equations were tested for fit according to the constituent muscles and sex. KES could be measured in 472 of the 520 participants (254 men and 218 women, mean age: 62.3 ± 10.3). Multiple linear regression analyses with age‐adjusted models were then used for evaluating the relationships between KES and quadriceps measurements. Results: All muscle CSAs and CTVs showed downward trends with age (men: P < 0.001 for all; women: vastus medialis CTV, P = 0.004; others, P < 0.001); the intermuscular adipose tissue CSA did not show any trend (men: P = 0.938; women: P = 0.139), although its percentage of the entire quadriceps area showed an upward trend in both sexes ( P < 0.001). Men exhibited a quadratic decline in the CSAs for the entire quadriceps area ( P = 0.016), total quadriceps muscles ( P = 0.021), the vastus medialis ( P = 0.010) and vastus lateralis ( P = 0.038), and all CTVs (rectus femoris, P = 0.044; others, P < 0.001). Women exhibited a quadratic equation in the CTV for rectus femoris ( P = 0.031), but a linear decline in the other variables ( P < 0.001 for all). Both the total quadriceps muscles CSA and CTV were significantly associated with KES in both sexes ( P < 0.001). For each muscle, the CSAs of the vastus medialis ( P < 0.001) and vastus intermedius ( P = 0.001) were significantly associated with KES in men, whereas the vastus medialis CSA ( P < 0.001), vastus lateralis CSA ( P = 0.006), rectus femoris CSA ( P = 0.020), and vastus intermedius CTV ( P = 0.025) were significantly associated with KES in women Conclusions: Age‐related quadriceps femoris changes in mass and quality differed by sex and the constituent muscles. The constituent muscles contributing to KES differed between men and women. Quadriceps CSA and CTV measurements are useful for objectively assessing age‐related and sex‐related muscle deterioration and KES.